An assessment of the impact of job satisfaction towards attainment of organisational goals: a case study of Zimbabwe National Statistics Agency (ZIMSTAT) - Haruzivi, Tatenda M. (Midlands State University, 2019)
No organisation can successfully achieve its goals and mission unless and until those who constitutes to its blooming are satisfied with their jobs. Thus, this research was primarily concerned with examining and exposing how job satisfaction is pulling back ZIMSTAT’s organisational goals attainment. ZIMSTAT is a statistics based organisation, therefore its employees are the most valuable assert which ensures productivity and organisational goals attainment. Nevertheless, its primary goal is to produce timely, accurate and official statistics in order to advance economic growth, development and advice the government on policy formulation. Thus, job satisfaction is the missing central part of the puzzle for ZIMSTAT, which has a vision of being the world-class producer of national statistics in Zimbabwe to attain its goals. Considering that job, satisfaction has been widely and deeply scrutinised shown by literature review the researcher pinpointed organisational functioning (operating system) as the gap, which needs attention. Thus, a complex set of instruments was used to gather data in form of interviews, questionnaires and observations. The research findings highlighted deep frustration, bitterness and anger amongst ZIMSTAT employees due to arrogance, manipulation and exploitation by the managerial and executive body. Hence, negative job satisfaction is a major threat haunting the attainment of organisational goals of ZIMSTAT. Eventually, ZIMSTAT is being advised to fully embrace the transformation process, which will place it on a strong footing to thwart negative job satisfaction, which is a major threat towards organisational goals attainment. Moreover, organisational politics should be dealt with accordingly as it has eroded positive job satisfaction, which is a pillar of strength towards attaining organisational goals.